Teaching Arabic To Non Arabic Speakers Using The Teaching Methods Of Prophet Muhammad/ تعليم اللغة العربية لغير الناطقين بها باستخدام طرق تعليم النبي محمد صلى الله عليه وسلم - M.H.A. Munas; A.M. Razick; M.C.S. Shathifa; A.R. Nasar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The Arabic language, the language of the Holy Qur’an, is one of the most widely spoken languages within the Semitic language group. Students learn Arabic as a second or foreign language worldwide for various reasons. Arabic language scholars have developed numerous methods to teach the Arabic language. This study utilizes the teaching methods used by the Prophet Muhammad to enhance the teaching of the Arabic language to non-Arabic speakers. The objectives of the research are to expose the methods of teaching adopted by Prophet Muhammad (peace be upon him) and propose a visionary method to enhance the effectiveness of teaching the Arabic language to non-native speakers. The study employed a descriptive-analytical deductive method. The data was obtained through library research, including books, magazines, previous research, and internet resources. The key findings of this research indicate that the teaching approach adopted by the Prophet is a holistic and interactive method for teaching the Arabic language to non-native speakers. This approach emphasizes teaching pronunciation of letters using the method of repetition; developing listening skills using the method of storytelling; enhancing teaching vocabulary and writing using proverbs, utilizing gestures, or using illustrations for clarification and statements; developing the skill of speaking using dialogue and discussion methods; and developing the reading skill by using the questioning and answer method during the teaching-learning process. More importantly, Prophet Muhammad focused on teaching methods to develop the skills of listening and speaking, as he was illiterate and unable to read and write. Hence, he engaged the audience by attracting their attention through oral communication.